(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
We have chosen Hemingway as representative for the post-WWI generation of American ex-pats who found refuge in Paris in the 20s and the 30s, disillusioned with the immoral outcomes of the war. He found in pen an escape from that society in decline and from the horrors experienced first-hand; he created resistance to the establishment and social conventions on their typewriters as they felt they had no place within traditional society. Writing became a power; writing is an action, a doing; In a world where the action is necessary, the means to do so is writing. We follow the writer’s search for identity, seen as a process of singularization based on recognizing that we share a common origin or circumstances with another person or community – the very community to which Gertrude Stein, F. Scott Fitzgerald, John Dos Passos, Sinclair Lewis, and Samuel Putnam belonged. None of them, at the time, would have imagined that the war was going to have such apocalyptic and catastrophic effects as it did. When the war ended, everything changed. However, those changes and life itself turn out to be as fleeting as the sunrise in Hemingway’s novel. Having (re)discovered their identity in Paris, many of them returned to a more disappointing than expected America